Exploring the Influence of Extended High-Frequency Hearing on Cochlear Functioning at Lower Frequencies. - Mishra, Srikanta K.; Rodrigo, Hansapani; Balan, Jithin R. (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Diminished basal cochlear function, as indicated by elevated hearing thresholds in the extended high frequencies (EHFs), has been associated with lower levels of click-evoked and distortion-product otoacoustic emissions measured at lower frequencies. However, stimulus-frequency otoacoustic emissions (SFOAEs) at low-probe levels are reflection-source emissions that do not share the same generation mechanism as distortion-source emissions. The primary objective of the present study was to examine the influence of hearing thresholds in the EHFs on SFOAEs measured at lower frequencies. Method: SFOAEs were recorded from both ears in 45 individuals with normal hearing thresholds in the conventional audiometric frequencies (0.25–8 kHz). Hearing thresholds were also measured at EHFs (10, 12.5, and 16 kHz). SFOAE magnitudes and signal-to-noise ratios (SNRs) were averaged across 1, 2, and 4 kHz probe frequencies and also averaged for high-probe frequencies (2 and 4 kHz). Results: SFOAE magnitudes and SNRs were significantly higher for ears with better EHF hearing relative to poorer EHF hearing, categorized based on the median split. In addition, hearing in the EHFs significantly contributed to the variance in all SFOAE measures, except for the high-frequency SFOAE magnitudes model. However, hearing thresholds at the probe frequencies did not significantly contribute to the variance in SFOAEs. Conclusions: The study findings suggest that alterations in the basal cochlea, as revealed by EHF hearing thresholds, could be associated with diminished cochlear functioning in relatively apical regions, shown by SFOAEs at lower frequencies, in individuals with normal audiograms. These findings underscore the significance of considering EHF thresholds in audiological evaluations, as alterations in these frequencies may reflect broader cochlear health status.